The Achievement Coaching Management Badminton Association Indonesia Lubuk Linggau City, South Sumatera Province (Journal of Physical Education and Sports, 2022)
The city of Lubuk Linggau, South Sumatra, has several sports that have the potential to win gold medals, one of which is badminton. This study aims to examine the problem of developing badminton achievement carried out by PBSI Lubuk Linggau. This research was a qualitative descriptive study. The method used in this research was POAC program management. Data collection techniques in this study was interviews, observation and documentation. Data analysis was carried out by means of data reduction, data presentation and then conclusions were drawn. Research Results: 1) The management planning system of the Indonesian Badminton Association (PBSI) in Lubuk Linggau City is very good which meets all aspects of the category. 2) The organizing system for the management of the Indonesian Badminton Association (PBSI) in Lubuk Linggau City is categorized as good, because it only meets 4 of the 5 aspects of the category. 3) The implementation system (actuating) for the management of the Indonesian Badminton Association (PBSI) in Lubuk Linggau City is very good, because it has fulfilled all aspects in the existing categories. 4) The management control system of the Indonesian Badminton Association (PBSI) in Lubuk Linggau City is categorized as good, because it only fulfills 3 aspects of the 4 existing categories. The conclusion of the research is that badminton in Lubuk Linggau City is good starting from planning, organizing, implementing and supervising activities.